Efektivitas Model Konseling Kelompok Cognitive-Behavior untuk Permasalahan Diri Peserta Didik: A Systematic Literature Review (SLR) - Susanto, Aisah Nareswari; Saputra, Askhar Dwista; Ardana, Ellena Pasya Nova; Puterisia, Gilga Jane Ady; Makhmudah, Ulya (TSAQOFAH, 2024)
Cognitive-Behavior Therapy (CBT) in dealing with students' psychological problems. The background to this research shows that there are psychological challenges faced by students, such as anxiety and depression, which can hinder their development. The aim of this study was to evaluate the effectiveness of CBT in a group context and understand the factors that influence its success. The method used is Systematic Literature Review (SLR), by collecting data from various academic sources to analyze findings related to CBT group counseling. The results showed that CBT group counseling significantly reduced anxiety and depression, and improved students' social skills. Peer support and a supportive school environment were shown to be important factors in the success of the intervention. The conclusions of this study confirm that the integration of therapeutic approaches with social support can produce positive changes in students' mental health, as well as provide a basis for the development of counseling programs in schools.